2015
DOI: 10.1038/srep09197
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced functional link between executive control network and reward network explain the online-game seeking behaviors in Internet gaming disorder

Abstract: Literatures have shown that Internet gaming disorder (IGD) subjects show impaired executive control and enhanced reward sensitivities than healthy controls. However, how these two networks jointly affect the valuation process and drive IGD subjects' online-game-seeking behaviors remains unknown. Thirty-five IGD and 36 healthy controls underwent a resting-states scan in the MRI scanner. Functional connectivity (FC) was examined within control and reward network seeds regions, respectively. Nucleus accumbens (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 61 publications
8
46
0
1
Order By: Relevance
“…IGD subjects without comorbid depression also showed stronger sgACC FC with the left dlPFC than the other groups. Aberrant functional interactions between brain networks have been proposed as part of the pathophysiology of IGD ( 64 , 65 ). Hyperconnectivity between the DMN and the central executive network may also be a neurobiological factor underlying IGD.…”
Section: Discussionmentioning
confidence: 99%
“…IGD subjects without comorbid depression also showed stronger sgACC FC with the left dlPFC than the other groups. Aberrant functional interactions between brain networks have been proposed as part of the pathophysiology of IGD ( 64 , 65 ). Hyperconnectivity between the DMN and the central executive network may also be a neurobiological factor underlying IGD.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was supported by a functional MRI study on IGD, which demonstrated decreased functional connectivity in the executive‐central network and increased functional connectivity in the reward‐associated networks(Dong et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Resting-state fMRI has emerged as a powerful tool to investigate intrinsic brain activity that is not confounded by task performance9 and has been used to investigate various psychiatric disorders, including IGD101112. Differences in resting-state functional connectivity (rsFC) have been linked to IGD including brain regions within or between the default mode network (DMN)1314, executive control network (ECN)1112, and reward network11151617.…”
mentioning
confidence: 99%